Translation Methods of Noun Phrases in "Everything, Everything" Novel by Nichola Yoon into Indonesian - Ni Made Verayanti Utami; I Gusti Agung Sri Rwa Jayantini; Adi, Ni Ketut Sri Atik Oktari (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This research deals with the translation method of noun phrase found in Everything, Everything novel by Nichola Yoon into Indonesian. This study aims to identify translation methods of noun phrases. The data were taken from Everything, Everything novel by Nichola Yoon. Theory of translation method by Newmark (1988) is used to analyze the data found. Descriptive qualitative method is used to analyze the translation methods of noun phrases. As the result, all the eight types of translation methods of noun phrases are found with total of the data are 776 data which is percentage were 70 data (9.0%) for Word-For- Word Translation, 139 data (17,9%) for Literal Translation, 516 data (66,5%) for Faithful Translation, 1 data (0,1%) for Semantic Translation, 1 data (0,1%) for Adaptation translation, 46 data (5,9%) for Free Translation, 2 data (0,2%) for Idiomatic Translation, and 1 data (0,1) for Communicative translation.